La competitividad empresarial: Un aporte al crecimiento económico y al desarrollo sostenible - Becerra Ossa, Jhennys Paola (Corporación Universitaria Americana, 2019)
The progress of a society depends to a great extent on the level of competitiveness of the business sector, since the investments and decisions of the private sector determine to a great extent the evolution and growth of the economy. Likewise, sustainable development must go substantially hand in hand with competitiveness, while simultaneously ensuring the maintenance of resources for future generations, in other words, it is not positive to be competitive while devastating the assets currently owned. The book "Business competitiveness: a contribution to economic growth and sustainable development" focuses on the analysis of those tools, situations, strategies and conditions that contribute to the economic and sustainable development of the Cordoba region.